Catalytic Conversion of Biomass to Furanic Derivatives with Deep Eutectic Solvents. Issue 6 (12th February 2021) - Chen, Binglin; Peng, Zhiqing; Li, Chuang; Feng, Yunchao; Sun, Yong; Tang, Xing; Zeng, Xianhai; Lin, Lu
Abstract: Biomass is the only renewable organic carbon resource in nature, and the transformation of abundant biomass into various chemicals has received immense spotlight. As a novel generation of designer solvents, deep eutectic solvents (DESs) have been widely used in biorefinery due to their excellent properties including low cost, easy preparation, and biodegradability. Although there have been some reports summarizing the performance of DESs for the transformation of biomass into various chemicals, few Reviews illuminate the relationship between the functional structure of DESs and catalytic conversion of biomass. Hence, this Minireview comprehensively summarizes the effects of the types of functional groups in DESs on catalytic conversion of biomass into furanic derivatives, such as carboxylic acid‐based hydrogen‐bond donors (HBDs), carbohydrate‐based HBDs, polyalcohol‐based HBDs, amine/amide‐based HBDs, spatial structure of HBDs, and various hydrogen‐bond acceptors (HBAs). It also further summarizes the effects of adding different additives into the DESs on the synthesis of high value‐added chemicals, including water, liquid inorganic acids, Lewis acids, heteropoly acids, and typical solid acids. Moreover, current challenges and prospects for the application of DESs in biomass conversion are provided. Abstract : Green media : Deep eutectic solvents (DESs) are used for conversion of biomass to various furanic derivatives. The whole process is green because the most of the DESs components are renewable, degradable, and low/non‐toxic.